Preparative isolation and purification of antioxidative diarylheptanoid derivatives from Alnus japonica by high-speed counter-current chromatography - Lim, Soon Sung; Lee, Min Young; Ahn, Hong Ryul; Choi, Soon Jung; Lee, Jae-Yong; Jung, Sang Hoon (WILEY PERIODICALS, INC, 2011)
This study employed the online HPLC-2,2'-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS)+ bioassay to rapidly determine the antioxidant compounds occurring in the crude extract of Alnus japonica. The negative peaks of the ABTS+ radical scavenging detection system, which indicated the presence of antioxidant activity, were monitored by measuring the decrease in absorbance at 734 nm. The ABTS+-based antioxidant activity profile showed that three negative peaks exhibited antioxidant activity. High-speed counter-current chromatography (HSCCC) was used for preparative scale separation of the three active peaks from the extract. The purity of the isolated compounds was analyzed by HPLC and their structures were identified by 1H- and 13C-nuclear magnetic resonance spectrometry (NMR), heteronuclear multiple bond correlation (HMBC), and heteronuclear single quantum correlation (HSQC). Two solvent systems composed of n-hexane/ethylacetate/methanol/water (4:6:4:6, v/v) and of ethyl acetate/methanol/water (1:0.1:1, v/v) were performed in high-speed counter-current chromatography. Consequently, a total of 527 mg of hirsutanonol 5-O-beta-D-glucopyranoside, 80.04 mg of 3-deoxohirsutenonol 5-O-beta-D-glucopyranoside, and 91.0 mg of hirsutenone were obtained with purity of 94.7, 90.5, and 98.6%, respectively.
Keywords: ABTS RADICAL-CATION; ONLINE; BARK; HIRSUTA; IDENTIFICATION; ISOFLAVONOIDS; EXPRESSION; LICORICE; CELLS; ESTER